Detection Method for Authenticity Assessment of Malaysian Tualang Honey Using Absorbance and Transmittance Analysis with combination of Application of Artificial Neural Network - Optical Properties (ANN-OP) Classification - Zakaria, Mohd Hazlan; Abdul Jamil , Muhammad Mahadi; Wan Zaki , Wan Suhaimizan; Joret , Ariffudin; Noor Azwan Shairi, (Journal of Electronic Voltage and Application, 2026)
Honey is a highly valued natural sweetener, frequently subjected to adulteration due to its economic importance. It is commonly consumed for its perceived health benefits and as a substitute for refined sugar in a wide range of food products. In Malaysia, the widespread availability of diluted honey poses a significant challenge in distinguishing between pure and adulterated forms. This study presents a simple spectrophotometric approach using absorbance and transmittance measurements to differentiate honey authenticity. Eight honey samples, both pure and adulterated, were analysed. Results showed that the darker honey samples exhibit higher absorbance values, while lighter samples demonstrate faster signal responses in transmittance measurements. Optimal wavelengths were identified at 480 nm for absorbance and 630 nm for transmittance. These wavelength-specific responses provide an effective means of identifying adulterated honey. This method offers a practical solution for consumers and industry professionals seeking to verify honey purity, especially for health and dietary applications.